POTENSI FINANSIAL TEKNOLOGI SYARIAH DALAM MENJANGKAU PEMBIAYAAN NON-BANK - FAWZI BHAKTI PRESTAMA; MUHAMMAD IQBAL; SELAMET RIYADI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
The purpose of this study is to analyze the potential of Crowdfunding and Peer-to-Peer Lending Financial Technology (FinTech) Sharia to reach the non banking financing. There are four Crowdfunding and Peer-toPeer LendingFinTech Sharia operators in Indonesia used as the sample. The data used in this study was obtained from direct interview with the FinTech operators and literature study of similar subject. The analysis method used in this study is SWOT analysis. The results of the study which used SWOT analysis model found that the Crowdfunding and Peer-to-Peer Lending FinTech Sharia are not a threat to existing Sharia financial institutions and can also increase the penetration of sharia financial industry in Indonesia because they offer cost efficiency, ease of access, speed of financing distribution, and the low rate of nonperforming financing. However, there are still small quantity of FinTech Sharia registered at OJK, no specific regulation for FinTech Sharia and no Sharia Supervision Board in many FinTech Sharia can be obstacles for FinTech Sharia operators.